Perception of figurative language in copywriting and its influence on buying behavior - Widhoyoko, Yudhistiro Pandu (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2023)
Copywriting is an important part of a marketing strategy because it can influence people's perceptions of the advertised product or service.One of the techniques often used in copywriting is figurative language, which is the use of words that are not in accordance with theirconventional meaning to create special effects or convey messages in a more compelling way.The purpose of this research is to find out theperceptions of Indonesian people towards figurative language in copywriting and its influence on buying behavior. Literature review showsthat using figurative language in copywriting can help increase advertising effectiveness, but it can also overcome message comprehension ifnot used properly.The research method used was a survey by distributing questionnaires to 100-200 people in Indonesia aged 18 years andover. The questionnaire will include questions about demographic information, perceptions of figurative language in copywriting, and theinfluence of figurative language on buying behavior. The data obtained will be analyzed descriptively and inferentially using statisticalsoftware. By conducting this research, it is hoped that it will provide deeper insight into the role of figurative language in copywriting andhow it influences people's perceptions and buying behavior.Keywords: Buying behavior, Copywriting, Figurative language, Perception